Digital Medical Image Enhanced by wavelet Illumination-Reflection Model - Xiong Jie (Institute of Advanced Engineering and Science, 2013)
When a digital medical image is enhanced, the useful details of the image should be strengthened， but the details can not be strengthened by these algorithms based on traditional illumination-reflection model. According to the imaging principle and medical requirement, wavelet illumination-reflection model and a new algorithm based on the model are proposed. The image is decomposed into illumination and reflection by wavelet illumination-reflection model. The details of the reflection are strengthened. The dynamic range of the illumination is reduced in order to enhance the image. Experiments and analysis show that the method is obviously better than Histogram Equalization, Homomorphic Filtering and multi-scales Retinex. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1866